Characteristics of Envelope Genes in a Chinese Chronically HIV-1 Infected Patient With Broadly Neutralizing Activity - Zhang, Dai; Zou, Sen; Hu, Yuanyuan; Hou, Jiali; Hu, Xintao; Ren, Li; Ma, Liying; He, Xiang; Shao, Yiming; Hong, Kunxue (Frontiers in Microbiology, 2019)
Exploring the characteristics of HIV-1 envelope glycoprotein (env) gene in the natural HIV-1 infected individual with broadly neutralizing activity may provide insight into the generation of broadly neutralizing antibodies and the design of an appropriate immunogen. Recently, a chronically HIV-1 infected patient with broadly neutralization activity was identified and a VRC01-class neutralizing antibody DRVIA7 (A7) was isolated from the patient. In the present study, 155 full length HIV-1 env gene fragments (including 68 functionally Env clones) were amplified longitudinally from plasma of six time points spanning 5 years in this donor. Viral features were analyzed by comparing Env clones of different time points, as well as 165 Chinese HIV-1 subtype B env sequences from HIV Sequence Database (Chinese B_database). Shorter V1 length, less potential glycan and lower ratio of NXT: NXS in gp160 were observed in the first five time points compared to that from the last time points, as well that from Chinese B_database. Sequence analysis and neutralization assay of Env-pseudoviruses showed that the increasing diversity of env sequences in the patient was consistent with the appearance and maturation of A7 lineage antibodies. The potent neutralization activity and viruses escaped from the neutralization of concurrent autologous plasma are consistent with higher residues variation at antibody recognition sites. Almost all viruses from the plasmas were neutralization-resistant to VRC01 and A7 lineage antibodies. For a chronically HIV-1 infected individual over ten years, we found that greater viral diversity, short V1 sequences and less potential N-linked glycosylation(PNGS) in V1, might be associated with the development of broadly neutralizing antibody responses.